Prevalence and impact of chronic oedema in a population of obese patients prior to and following bariatric surgery - Newman, Amy M. (2018)
Background Chronic oedema (persistent swelling) is a common, often unreported, condition, which can have severe social and psychological implications for individuals and their families. Oedema can be especially problematic for obese patients, who often struggle with: immobility, co-morbidities, and the inability to lose weight.